IMPLEMENTASI EKSAMINASI TERHADAP PUTUSAN HAKIM: Implementation Of Examination Of Judge's Decision - Apriani, Titin (Ganec Swara, 2025)
The purpose of this study is to determine how the implementation of the examination of a judge's decision that is late in having permanent legal force and whether the implementation of the examination can cancel the judge's decision. This study is alibrary research that uses data in the form of books, laws, articles, journals, several examples of judge's decisions that have permanent legal force that are examined, while the technique and data collection is by collecting various ideas, theories and concepts from various literature that emphasizes the process of comparison between arguments, articles or other laws. The approach method used in this study is the statute approach and the conceptual approach and the case approach. The research results show that examinations are not new in the world of justice. In 1967, when Soerjadi was Chief Justice, the Supreme Court issued Supreme Court Circular Letter (SEMA) No. 1 of 1967, which instructed the Chief Justice of the District Court to conduct examinations of cases decided by judges within its jurisdiction. This examination was issued as a mechanism or as a form of oversight of the products issued by the court or judge in deciding a case. Therefore, an examination cannot overturn a decision issued by a judge, but the decision can be overturned through legal remedies such as appeal, cassation, and judicial review